Potensi Ekstrak Daun Kirinyuh (Chromolaena odorata L.) sebagai Bioherbisida Gulma Cacabean (Ludwigia sp.) - Elma Nor Khaliza Khaliza; Lyswiana Aphrodyanti Aphrodyanti (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Cacabean weed (Ludwigia sp.) is an invasive weed that disrupts the growth of main crops such as rice and corn. This research aims to assess the effectiveness of kirinyuh leaf extract (Chromolaena odorata L.) as a bioherbicide in suppressing the growth of Ludwigia sp. using concentrations of 25%, 50% and 75%. The research was designed using a Completely Randomized Design (CRD) with five treatments and four replications. The results showed that kirinyuh leaf extract had a significant effect on the phytotoxicity of Ludwigia sp., with symptoms of chlorosis, necrosis and tissue death. A concentration of 75% shows the highest effectiveness, equivalent to herbicides containing the active ingredient glyphosate. These findings show the potential of kirinyuh leaf extract as an environmentally friendly bioherbicide.